Psycho-oncology in India: Emerging trends from Kerala - Venkateswaran Chitra, Kumar T Manoj (Indian J Palliat Care 2006;12:34-38, 2006)
It is estimated that around 2.5 million people suffer from cancer at any given time in India. Almost 80 per cent of patients reach hospitals in advanced stages of the disease. The majority needs palliative care, whereas only a minority of the needy receives this input. The challenge in the developing world is to evolve a culturally and socio-economically appropriate and acceptable system of care, while addressing psychosocial issues along with long-term care needs, that is accessible to the majority of those who need it. The evolution of a specific service for psychosocial care for persons and families started in the 1970s, initial work focusing mainly on research. Contributions from persons in varied topics have been outlined. Only a few organized clinical services function as part of large tertiary hospitals, oncology centers or palliative care units. The emerging trend in Northern Kerala is based on an integrated service linking training, clinical services and research activities which are linked at several levels, involving volunteers in the community. Future hopes lie in developing core groups; establishing specific clinical services liaising with cancer care teams, large scale research projects and discussion with policy makers to develop guidelines at national level.